2018
DOI: 10.3151/jact.16.282
|View full text |Cite
|
Sign up to set email alerts
|

The Top-Bar Effect in Specimens with a Single Casting Point at One Edge in High-Performance Self-Compacting Concrete

Abstract: An investigation of the steel-to-concrete bond in high-performance self-compacting concrete (HPSCC) is presented based on direct pull-out tests. The investigation was performed on specimens made of three different HPSCC mixes with varying contents of silica fume (without, 5 and 10% by mass of cement). Specifically, the top-bar effect in specimens with a single casting point at one edge was examined. Horizontal specimens with transverse rebars distributed over their heights (480 mm) and lengths (1600 mm) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Silica fume is a by-product of the silicon metals production. It is used in the production of additives for cement mortars, industrial concrete, insulation materials, ceramic products, products with an increased resistance to high temperature and high-performance self-compacting concrete [ 29 ]. It has been reported that industrial waste and numerous artificial and natural fibers can be successfully utilized to enhance the properties of concrete [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silica fume is a by-product of the silicon metals production. It is used in the production of additives for cement mortars, industrial concrete, insulation materials, ceramic products, products with an increased resistance to high temperature and high-performance self-compacting concrete [ 29 ]. It has been reported that industrial waste and numerous artificial and natural fibers can be successfully utilized to enhance the properties of concrete [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to ordinary concretes, the designing process of HPSCC mix is determined by the increased cement content, superplasticizers, and an additive of reactive materials, i.e., silica fume. HPSCC is thus characterized by its ability to fill a form with congested steel rebars and self-leveling without mechanical compaction and it yields exceptionally high strength and durability [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a study conducted on 1500 mm high columns, [12] made of normal and self-compacting concretes with a varying water-to-cement ratio, the reduction of ultimate bond stress for self-compacting concretes ranged between 32%-55% and from 60% to 74% for normal concretes. However, it has been noted [20] that modification of self-compacting concrete with silica fume in an adequate amount-less than 10%-in relation to the cement mass practically eliminates bond reduction along the height.…”
Section: Introductionmentioning
confidence: 99%